Predicting Disease Activity Score in Rheumatoid Arthritis Patients Treated with Biologic Disease-Modifying Antirheumatic Drugs Using Machine Learning Models - Salehihafshejani, Fatemeh; Zarifi, Sara; Bayat, Sara; Habibpour, Mahdis; Asemanrafat, Amirreza; Kleyer, Arnd; Schett, Georg; Fritsch-Stork, Ruth; Eskofier, Björn (Technologies, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease marked by joint inflammation and progressive disability. While biological disease-modifying antirheumatic drugs (bDMARDs) have significantly improved disease control, predicting individual treatment response remains clinically challenging. This study presents a machine learning approach to predict 12-month disease activity, measured by DAS28-CRP, in RA patients beginning bDMARD therapy. We trained and evaluated eight regression models, including Ridge, Lasso, Support Vector Regression, and XGBoost, using baseline clinical features from 154 RA patients treated at University Hospital Erlangen. A rigorous nested cross-validation strategy was applied for internal model selection and validation. Importantly, model generalizability was assessed using an independent external dataset from the Austrian BioReg registry, which includes a more diverse, real-world RA patient population from across multiple clinical sites. The Ridge regression model achieved the best internal performance (MAE: 0.633, R2: 0.542) and showed strong external validity when applied to unseen BioReg data (MAE: 0.678, R2: 0.491). These results indicate robust cross-cohort generalization. By predicting continuous DAS28-CRP scores instead of binary remission labels, our approach supports flexible, individualized treatment planning based on local or evolving clinical thresholds. This work demonstrates the feasibility and clinical value of externally validated, data-driven tools for precision treatment planning in RA.
CRIS-Team Scopus Importer:2025-09-05
Keywords: bDMARDs; DAS28 CRP; machine learning; regression models; remission prediction; rheumatoid arthritis